Methodological foundations of formation of the educational environment at the higher military educational institutions of aviation profile - Marchenko, O. (Problems of Engineer-Pedagogical Education, 2018)
It is identified a complex integrative character of the pedagogical phenomenon of the education al environment, it is defined he system properties and proven the social nature, integrity, dynamism, openness. It is demonstrated the expediency of competence, the acme logical methodological approaches in there solution of educational environment formation problem sat higher military educational establishment so aviation profile. It is defined the main methodological provisions for the professional competencies formation and achieved the personal development peaks of the future specialists of the military aviation profile It is proved that the formation of motivational-value, social, communicative, cognitive-activity, personal and developmental components of the professional competence of the future military pilots and the aviation engineers supported the integration of the educational environment at the higher military educational institution of the aviation profile in the socio-cultural space, the existence of the personal grow thin captives and the professional formation, translation and assimilation of universal humanistic values, implementation of training standards, ensuring a high level of intellectual, physical, cultural ones.